MEANINGFUL LITERACY THROUGH L2 POETRY WRITING: THE PERCEPTION AND EXPERIENCE OF INDONESIAN EFL LEARNERS - Nur Amalina, - (2022)
This qualitative case study aims to investigate how language learners experience L2 poetry writing and how it affects their self-perception as English writers. The participants of the study were three advanced Indonesian EFL learners. The study focusses on learners' poetry writing strategies, their poetic identities in the poems, and their self-perceptions post-poetry writing. The instruments used in the study were questionnaires and writing reflections, semi-structured interviews, and participants' poems. The findings indicated that management to their self-perceived skill, emotions and identities. Learners' strategy use reflects their desire for enjoyment, showmanship and sense of camaraderie with fellow learner writers. Further, the poetic identity analysis of learners' poems illustrated how their writing styles are shaped by their writing values and their subject positions. The writing styles reflect each learner's existing and imagined identities, their enactment of agency to experiment with irregularity in English language, and their attempt to communicate with readers by making meticulous language choices. In the end, the participants experienced poetry writing as both self-enriching experience as well as socially-conscious experience. However, the positive poetry writing experience did not drastically change their self-perception as English writers. This study provides evidence how learners' self-perceived identities as English writers/user and learners are dynamic and complex. Language learners can navigate their identities between being language users and learners to improve their skill whilst harnessing confidence to showcase it. In addition, the analysis of learners' experience and self-perception unveiled the values of poetry writing as meaningful literacy practice. By noting learners' experience, perceptions and poetry writing' values, this study offers a schematic outline of poetry writing pedagogy which can be practically applied in EFL teaching.